System dynamics modeling of the safety evolution of blended-wing-body subscale demonstrator flight testing. (November 2016) - Lu, Yi; Zhang, Shu-Guang; Hao, Lian; Huangfu, Hua-Yan; Sheng, Hang
Highlights: Modeled the risk dynamics of a "fly-fix-fly" organizational safety behavior in aviation. System dynamics modeling represented the safety records of BWB unmanned subscale demonstrator flight testing. Explained why previous post-accident learning was ineffective and improvement benefits were delayed. Shows a socio-technical safety vision integrating technical and organizational dimensions. Abstract: Between 2008 and 2010, three blended-wing-body (BWB) aircraft configuration subscale demonstrators developed by our research team encountered frequent accidents in flight tests. After the crash of the third demonstrator in March 2010, we initialized a systematic safety control approach and achieved improved safety records on the fourth demonstrator in 2012. This paper aims to develop a system dynamics model to represent such safety evolution process and to reveal the organizational mechanism involving complex dynamic interactions of accident causal factors (technical, organizational and human). Using VENSIM® software as a modeling tool, a qualitative system dynamic simulation is performed to model the feedback relationships of safety-related variables that affect the accident rate of demonstrator flight testing across time. This paper gives an innovative example to apply system dynamics methodology on accident causation analysis in the area of aviation.